Dicephalus Parapagus Conjoined Twins Diagnosed by First-Trimester Ultrasound - Keiko Watanabe; Masanori Ono; Mayu Shirahashi; Toshiyuki Ikeda; Kazumi Yakubo (Hindawi Limited, 2016)
Conjoined twins are a rare phenomenon, occurring in 1% of monochorionic twin gestation, with an incidence of 1 : 50 000 to 1 : 100 000. Many conjoined twins have abnormalities incompatible with life, so early prenatal diagnosis is very important for optimal management of both pregnancy and delivery. We report a case of dicephalus parapagus conjoined twins, sharing a single heart, diagnosed at 12 weeks' gestation. With early ultrasound diagnosis, we were able to provide appropriate and timely prenatal counseling to the family.